Peer effects in stock market participation: Evidence from immigration - Anastasia Girshina; Thomas Mathä; Michael Ziegelmeyer (European Central Bank (ECB), 2019)
This paper studies how peers' financial behaviour affects individuals' own investment choices. To identify the peer effect, we exploit the unique composition of the Luxembourg population and use the differences in stock market participation across various immigrant groups to study how they affect stock market participation of natives. We solve the reflection problem by instrumenting immigrants' stock market participation with lagged participation rates in their countries of birth. We separate the peer effect from the contextual and correlated effects by controlling for neighbourhood and individual characteristics. We find that stock market participation of immigrant peers has sizeable effects on that of natives. We also provide evidence that social learning is one of the channels through which the peer effect is transmitted. However, social learning alone does not account for the entire effect and we conclude that social utility might also play an important role in peer effects transmission.
Keywords: G5; D14; D83; G11; I22; 330; peer effects; stock market participation; social utility; social learning